INTEGRATING LITERATURE INTO ENGLISH LANGUAGE TEACHING: ENHANCING CRITICAL THINKING THROUGH SHAKESPEAREAN TEXT - Abdullayeva Gavkharoy Sultonmakhmud kizi (Modern American Journals, 2025)
The integration of literature, particularly canonical texts like those of William Shakespeare, into English Language Teaching (ELT) offers more than linguistic development—it fosters critical thinking, cultural awareness, and interpretive skills. This paper explores how literary analysis in ELT classrooms can enhance students' engagement and cognitive abilities, with a specific focus on Shakespeare’s plays. Drawing from both pedagogical theory and literary analysis, this article suggests practical strategies for using literature in EFL (English as a Foreign Language) contexts, ensuring both linguistic and intellectual enrichment.
Keywords: Literature in ELT, Shakespeare, critical thinking, language pedagogy, literary analysis, English language teaching, EFL learners